Paroles de banlieues : pour une redéfinition artistique des imaginaires - Ophélie Naessens (Itinéraires)
Since the 1990s, some artists go out to meet the inhabitants of so-called “sensitive” neighborhoods, working to deconstruct our imaginary of suburbs. In a context of urban riots, Suzanne Lacy (The Roof Is On Fire, 1994), Frédéric Moser and Philippe Schwinger (France, détours, 2009), decide to create from teenagers words. Through the study of these two examples, we will discuss how art could host a new form of dissonance, with the exploration of novel speeches and the displacement of representations.